Meningococcal disease in the Middle East and Africa: Findings and updates from the Global Meningococcal Initiative. - (:unkn) unknown (My University, 2017)
The Global Meningococcal Initiative (GMI) has recently considered current issues in Middle Eastern and African countries, and produced two recommendations: (i) that vaccination of attendees should be considered for some types of mass-gathering events, as some countries mandate for the Hajj, and (ii) vaccination of people with human immunodeficiency virus should be used routinely, because of increased meningococcal disease (MD) risk. Differences exist between Middle Eastern and African countries regarding case and syndrome definitions, surveillance, and epidemiologic data gaps. Sentinel surveillance provides an overview of trends and prevalence of different capsular groups supporting vaccine selection and planning, whereas cost-effectiveness decisions require comprehensive disease burden data, ideally counting every case. Surveillance data showed importance of serogroup B MD in North Africa and serogroup W expansion in Turkey and South Africa. Success of MenAfriVac® in the African "meningitis belt" was reviewed; the GMI believes similar benefits may follow development of a low-cost meningococcal pentavalent vaccine, currently in phase 1 clinical trial, by 2022. The importance of carriage and herd protection for controlling invasive MD and the importance of advocacy and awareness campaigns were also highlighted.
Keywords: African Research